Young people with HIV/AIDS: their resources for coping with suicide risk (2019)
Studying human behavior in its complexity is a constant task that demands rigor and the responsibility of integrating its findings to the understanding of social realities. This is the purpose of this book, the product of a qualitative study, justified by the incidence of HIV/AIDS and suicide in young people, mental health events that have been addressed from the psychosocial by researchers and organizations and entities who seek to deepen the study of their risk factors, for the structuring and implementation of public policies for prevention and intervention in these cases. The book exposes, in its first part, the antecedents of the problematic and the relevance, the importance and the scopes of the study, to then expand theoretically and empirically each one of the examined categories of analysis (i. e., HIV/ AIDS, suicidal ideation, suicidal behaviours and coping). It also shows the methodological procedure used: from an open interview, the experiences of a group of young people with HIV/AIDS are analysed. With this, we identify suicidal ideations and desires that affect their quality of life, but also a set of cognitive, emotional and behavioural internal resources that contribute to the coping process, necessary to continue life with the human immunodeficiency virus, are also evidenced and described. It is concluded that these young participants, despite the impact and emotional pain generated from the diagnosis —added to the stress caused by stigmatization, rejection, discrimination, and guilt— have internal resources and mechanisms that allow them to continue with their project. lifetime.